PERBANDINGAN FRAMEWORK SVELTE JS DENGAN REACT JS TERHADAP PERFORMA WEB APPLICATION BERBASIS JAVASCRIPT - Zulhijaya, Zulhijaya; Mustari S Lamada; Abdul Wahid (CV. Denasya Smart Publisher, 2025)
Comparison of Svelte JS Framework with React JS on Javascript-Based Web Application Performance. Informatics and Computer Engineering Education Study Program, Informatics and Computer Engineering Department, Faculty of Engineering, Makassar State University, (supervised by Mustari Lamada and Abdul Wahid). Comparison of Svelte JS and React JS frameworks using GTMetrix and WebPageTest tools by taking performance parameters including first contentful paint, speed index, large contentful paint, time to interactive, total blocking time, and cumulative layout shift. Each framework was tested by creating a 3-page website that had different loads. The test results were converted into scores where the score range was 1-3 for each parameter tested. React JS gets a total score of 26, 25, and 28 for each page. Svelte JS gets a total score of 34, 34, and 33 for each page. Native JS gets a total score of 34, 33, and 33 for each page. From these scores, it can be concluded that the Svelte JS framework is faster than React JS.